Simulation of the influence of parameters of disturbing vibration accelerations on the operation of a new two-channel transformer gravimeter - Bezvesilnaya, E.N.; Kyrychuk, Y.V.; Hrynevych, M.S.; Tolochko, T.A. (Акад. Е.А. Бөкетов ат. Қарағанды ун-ті КЕАҚ баспасы, 2023)
A new two-channel transformer gravimeter of an automated aviation gravimetric system was considered, the accuracy of which is higher than gravimeters known today. Its design was described. The influence of the parameters of disturbing vibrational accelerations on the operation of a new two-channel transformer gravimeter was simulated. The influence of frequencies and amplitudes of perturbing accelerations for the most unfavorable resonant cases on the operation of a two-channel transformer gravimeter was studied using a computer. After all, today there are no scientific, theoretical and practical works devoted to researching the possibility and expediency of using a two-channel transformer gravimeter as an AGS gravimeter. The transformer gravimeter contains a sensitive element consisting of a magnetic circuit, a movable armature, a primary excitation winding and a secondary output winding having two identical sections. Two sections of the secondary winding are connected in series-opposite, and the movable armature is connected to the motor, which, with a certain period, lowers the armature down and lifts it up along the magnetic circuit, and the motor is controlled by a switching device connected to the control voltage source, and the output signal from the secondary output winding is fed to the input of the output signal calculator, where an output signal is generated that is proportional to twice the value of the gravitational acceleration. A transformer gravimeter is a means of measuring the vertical component of the gravitational acceleration vector from an aircraft and can be used in the field of geodesy, geophysics, in particular, in the formation of reference gravimetric grids in hard-to-reach areas of the globe, as well as in aircraft and rocket building. The transformer gravimeter is part of the aviation gravimetric system placed on the aircraft.
Жаңа екі каналды трансформер гравиметрінің жұмысындағы бұзылған діріл үдеуі параметрлерінің әсерін модельдеу
Моделирование влияния параметров возмущающих вибрационных ускорений на работу нового двухканального трансформаторного гравиметра
Keywords: two-channel transformer gravimeter; disturbing action; resonant modes; damping; gravitational acceleration